Offering Management in Funeral Liturgy - Bungkaes, Yerlin; Mawikere, Marde Christian Stenly; Tuela, Anita I (Peneliti.net, 2025)
This study investigates the theological and practical dimensions of offering management in the funeral liturgy of the Evangelical Christian Church in Talaud (GERMITA), with a specific focus on the Maranatha Mangaran congregation. Traditionally, GERMITA’s official funeral liturgy does not include offerings as a component of worship, despite their theological significance throughout biblical tradition. However, the Maranatha Mangaran congregation has adopted this practice, raising important questions about liturgical flexibility, contextual theology, and pastoral care. Using a qualitative descriptive-analytical approach, data were collected through in-depth interviews with church leaders and members, participant observation during funeral services, and document analysis of liturgical regulations and church council decisions. Findings indicate that incorporating offerings into funeral liturgies holds deep theological meaning as an act of gratitude to God and also serves practical functions. It supports grieving families financially and enhances congregational solidarity. The practice reflects the church’s mission to serve both spiritual and material needs of its community. This research suggests that church leaders consider formal integration of offerings into funeral worship, as it embodies a meaningful theological response and addresses pastoral realities. The study contributes to ongoing discourse on contextual liturgy and strengthens the relevance of worship practices within GERMITA.